Multi-Objective Optimization of Regularized Self-Attention Regression Models Using NSGA-II: A Methodological Framework - Maja CZYŻEWSKA (Communications of International Proceedings, 2025)
Forecasting financial time series with deep neural networks requires models that are both expressive and well regularized. Regularized Self-Attention Regression (RSAR) is a hybrid architecture that combines LSTM, self-attention and convolutional components with explicit regularization, and has shown promising results in financial price prediction. However, its original formulation relies on a small number of manually selected hyperparameter configurations and a single-objective tuning strategy, which limits its adaptability to datasets with different volatility levels, noise structures and temporal dynamics. This paper addresses that gap by proposing a methodological framework that extends RSAR with multi-objective hyperparameter optimization based on an evolutionary genetic algorithm (NSGA-II). The framework defines a structured decision vector for key architectural and regularization parameters, formulates a bi-objective problem that jointly minimizes validation error and the train–validation gap, and outlines the optimization procedure built on non-dominated sorting, diversity preservation and elitist selection. The contribution is purely methodological: the paper provides a detailed description of the RSAR architecture, the underlying self-attention and regularization mechanisms, and their integration into a multi-objective search procedure. The resulting framework offers an implementation-ready basis for automatically adapting RSAR models to diverse financial markets, explicitly balancing predictive accuracy and overfitting risk. Experimental evaluation is intentionally omitted and will be presented in a subsequent study.
Keywords: Deep Neural Networks; LSTM; CNN; RSAR; Finance; Multi-objective optimization; NSGA-II